Emerging Concepts in Immune Thrombotic Thrombocytopenic Purpura - Laghmouchi, Aicha; Graça, Nuno A. G.; Voorberg, Jan (Frontiers in Immunology, 2021)
Immune thrombotic thrombocytopenic purpura (iTTP) is an autoimmune disorder of which the etiology is not fully understood. Autoantibodies targeting ADAMTS13 in iTTP patients have extensively been studied, the immunological mechanisms leading to the breach of tolerance remain to be uncovered. This review addresses the current knowledge on genetic factors associated with the development of iTTP and the interplay between the patient’s immune system and environmental factors in the induction of autoimmunity against ADAMTS13. HLA-DRB1*11 has been identified as a risk factor for iTTP in the Caucasian population. Counterintuitively, HLA-DRB1*08 was recently identified as a risk factor in the Japanese population. In vitro MHC class II peptide presentation experiments suggest that an ADAMTS13-derived peptide may bind to both HLA-DRB1*11 and HLA-DRB1*08 through different anchor-residues. It is apparent that iTTP is associated with the presence of infectious microorganism, viruses being the most widely associated with development of iTTP. Infections may potentially lead to loss of tolerance through molecular mimicry. In this model we propose that infections promote exposure of antigen presenting cells in the mucosa-associated lymphoid tissue to microbiota through disruption of epithelial barriers in the gut or lung. This may result in breach of tolerance through the presentation of microbiota-derived peptides that are homologous to ADAMTS13 on risk alleles for iTTP.